Case Report: Refractory Cytopenia With a Switch From a Transient Monosomy 7 to a Disease-Ameliorating del(20q) in a NHEJ1-Deficient Long-term Survivor - Poyer, Fiona; Jimenez Heredia, Raúl; Novak, Wolfgang; Zeitlhofer, Petra; Nebral, Karin; Dworzak, Michael N.; Haas, Oskar A.; Boztug, Kaan; Kager, Leo (Frontiers in Immunology, 2022)
We report the extraordinary case of a male Pakistani patient with a homozygous loss of function mutation in the non-homologous end-joining factor 1 (NHEJ1) gene. The growth retarded and microcephalic boy with clinodactyly of both hands and hyperpigmentation of the skin suffered from recurrent respiratory infections. He was five and a half years old when he came to our attention with refractory cytopenia and monosomy 7. Hematopoietic stem cell transplantation was considered but not feasible because there was no suitable donor available. Monosomy 7 was not detected anymore in subsequent bone marrow biopsies that were repeated in yearly intervals. Instead, seven and a half years later, a novel clone with a del(20q) appeared and steadily increased thereafter. In parallel, the patient's blood count, which had remained stable for over 20 years without necessitating any specific therapeutic interventions, improved gradually and the erythropoiesis-associated dysplasia resolved.